A novel inhibitor of the jasmonic acid signaling pathway represses herbivore resistance in tea plants. Issue 1 (19th January 2022) - Lin, Songbo; Ye, Meng; Li, Xiwang; Xing, Yuxian; Liu, Miaomiao; Zhang, Jin; Sun, Xiaoling
Abstract: The jasmonic acid (JA) signaling pathway plays a vital role in mediating plant resistance to herbivores . The tea plant ( Camellia sinensis ) is one of the most important woody cash crops in the world. Due to the lack of genetic transformation systems for tea plants, how the JA signaling pathway works in tea plants has not yet been determined. Now, with the development of cross-disciplines, chemical biology provides new means for analyzing the JA signaling pathway. In the present study, the structure of the small-molecule isoquinoline compound ZINC71820901 (lyn3) was obtained from the ZINC molecular library through virtual screening based on the structure of the crystal COI1-JAZ1 co-receptor and was found to act as an inhibitor of the JA signaling pathway in both Arabidopsis and tea plants. Our results revealed that lyn3 repressed tea plant resistance to Ectropis grisescens mainly by decreasing the accumulation of (−)-epicatechin and (−)-epigallocatechin via repression of the JA signaling pathway, which functioned in a modulation manner different from that of the already known inhibitor salicylhydroxamic acid (SHAM). As a novel inhibitor of the JA signaling pathway, lyn3 provides a specific option for further research on the JA pathway.